Teacher Experiences in Educating Students with Visual Impairments in Exact and Natural Sciences Lessons: A Scopus Literature Review - Geležinienė, Renata; Kuginytė-Arlauskienė, Ieva (Special Education, 2025)
This article examines the challenges faced in educating students who have visual impairments and teachers’ experiences in seeking solutions in the field of exact and natural sciences. The study aims to answer the following questions: What challenges do teachers encounter when teaching students with visual impairments in the field of exact and natural sciences? What technical and methodological solutions are employed to overcome these challenges in order to ensure the quality of inclusive education? The research problem was investigated by using a Scopus-based literature review method. The findings have revealed that many challenges are caused by the inaccessibility of visual teaching materials, which makes it difficult for teachers to convey the lesson content and for students to master it, since a substantial proportion of learning materials is represented by visual elements such as graphs, charts, and diagrams. The review of studies has revealed that the most efficient solutions are those based on a comprehensive approach, combining the use of multisensory modalities, personalized learning, and active student engagement. Such a strategy not only helps reduce obstacles but also enhances students’ motivation and promotes their autonomy. This is essential for creating inclusive educational practices in which students who have visual impairments can not only participate on an equal footing but also successfully realize their potential.